Screening for ADHD-Related Symptoms in Preschoolers Should Be Considered—Results From a Representative Sample of 5-Year-Olds From a German Metropolitan Region - Mechler, Konstantin; Krömer, Thomas; Landauer, Michael; Dittmann, Ralf W.; Häge, Alexander (Frontiers in Psychiatry, 2018)
Background: Early assessment and intervention are crucial to alleviate symptoms and prevent long-term negative outcomes in children suffering from Attention-deficit/hyperactivity disorder (ADHD). In Germany, at present, no standardized screening for ADHD is routinely administered. This study aims to evaluate a potential screening measure in a study population that is representative for a primary school entrance exam population in a German metropolitan region. Methods: Based on various socio-demographic variables, a sample of n=500 5-year-old children (58% boys, 42% girls), representative of a primary school entrance exam population from a German metropolitan region, was selected. Their parents completed a written survey consisting of the CBCL and a brief screening tool for ADHD symptomatology based on the DISYPS-II questionnaire. Demographic data were also collected. Results: The subscale “Attention problems” of the CBCL/4-18 showed results in the clinical range for n=10 (2%) participants. The ADHD screening identified n=23 (4.6%) participants as suspect of having ADHD with a statistically significant gender difference (n=17 boys vs. n=6 girls, p=0.03). In n=5 (1%) participants, all boys, both CBCL/4-18 and the ADHD screening were indicative of ADHD. Conclusions: Results indicate that screening for ADHD in this population may be both feasible and reasonable given the high prevalence and chronic nature of this disorder and the benefit of an early initiation of treatment. Results match previously reported figures for prevalence of ADHD-related symptoms and gender differences in preschool and older pediatric populations and thus do not support the hypothesis that the prevalence of ADHD in a metropolitan region is significantly higher than in other regions.